Cadmium removal capacities of filamentous soil fungi isolated from industrially polluted sediments, in La Plata (Argentina) - Massaccesi, Guillermina (2002)
Aspergillus terreus, Cladosporium cladosporioides, Fusarium; oxysporum, Gliocladium roseum, Penicillium spp., Talaromyces helicus and Trichoderma; koningii were isolated from heavily polluted streams near an industrial area in La Plata, Argentina. The fungi were obtained from sediments with 0.25–0.50 mg Cd/l and they were isolated in cadmium-basal medium. They were then cultivated to evaluate their Cd detoxification abilities. The biomass developed in static assays represented 5–53% of the yield of stirred cultures, for the different fungal species, although the cadmium absorption were similar in both cases. These soil fungi represented 50% of the total isolates and their mycelial growth was conspicuous in these polluted sediments. Although bacteria have been mentioned as active microorganisms against heavy metals, the mycelial fungi were able to develop a significantly higher mass to sequestrate more metals. Thus, they could be used in remediation biotechnology to improve the Cd detoxification of chronically contaminated habitats.